2001
DOI: 10.1128/iai.69.8.5121-5130.2001
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-Specific Protease fromPorphyromonas gingivalisActivates Protease-Activated Receptors on Human Oral Epithelial Cells and Induces Interleukin-6 Secretion

Abstract: Periodontitis is a chronic inflammatory disease affecting oral tissues. Oral epithelial cells represent the primary barrier against bacteria causing the disease. We examined the responses of such cells to an argininespecific cysteine proteinase (RgpB) produced by a causative agent of periodontal disease, Porphyromonas gingivalis. This protease caused an intracellular calcium transient in an oral epithelial cell line (KB), which was dependent on its enzymatic activity. Since protease-activated receptors (PARs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
250
2
19

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(283 citation statements)
references
References 59 publications
12
250
2
19
Order By: Relevance
“…Oral epithelial cells in culture strongly expressed PAR-1 and PAR-2 mRNA, weakly expressed PAR-3 mRNA, and did not express PAR-4 mRNA, as assessed by RT-PCR analysis (Fig. 4A), which was consistent with the findings of immunohistochemistry using sections of human gingival tissues (9). By flow cytometric analyses, weak expression of PAR-2 was detected on the untreated cell surface, but the expression of PAR-1 and -3 on the cell surface was below the detectable limit (Fig.…”
Section: Analysis Of the Par Family In Oral Epithelial Cells And Indusupporting
confidence: 76%
See 1 more Smart Citation
“…Oral epithelial cells in culture strongly expressed PAR-1 and PAR-2 mRNA, weakly expressed PAR-3 mRNA, and did not express PAR-4 mRNA, as assessed by RT-PCR analysis (Fig. 4A), which was consistent with the findings of immunohistochemistry using sections of human gingival tissues (9). By flow cytometric analyses, weak expression of PAR-2 was detected on the untreated cell surface, but the expression of PAR-1 and -3 on the cell surface was below the detectable limit (Fig.…”
Section: Analysis Of the Par Family In Oral Epithelial Cells And Indusupporting
confidence: 76%
“…Three of them (PAR-1, PAR-3, and PAR-4) are activated mainly by thrombin; the fourth (PAR-2) is activated by other serine proteinases such as trypsin, tryptase, and factor Xa (1)(2)(3). It is reported that more than one family member can be present in the same cell: human platelets express PAR-1 and PAR-4 (4, 5); mouse platelets express PAR-3 and PAR-4 (6); human endothelial cells express PAR-1, PAR-2, and possibly PAR-3 (7,8); and human oral epithelial cells express PAR-1, PAR-2, and PAR-3 (9). PAR-1 is the most widely expressed receptor among PAR family members in humans and mice, and it is reported that PAR-1 on human platelets and endothelial cells is inactivated by neutrophil serine proteinases, human leukocyte elastase (HLE), cathepsin G (Cat G), and proteinase 3 (PR3), by cleavage downstream of the tethered ligand (10).…”
mentioning
confidence: 99%
“…The effects of these aeroallergen proteases, acting via protease-activated receptors (PARs), 3 have been implicated in the regulation of the release of proinflammatory cytokines, such as eotaxin, GM-CSF, IL-6, and IL-8, by epithelial cells in a nonallergic inflammatory response (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). PARs appear to play a proinflammatory role by activating proinflammatory cytokines (11,12). A variety of proinflammatory cytokines are released from the airway epithelium, all of which have the potential to contribute to respiratory diseases, such as asthma, bronchiectasis, and chronic obstructive pulmonary diseases (13,14).…”
mentioning
confidence: 99%
“…Rgps are capable of activating PAR-2 expressed on human gingival epithelial cells, which produce proinflammatory cytokines [21]. We examined the possible involvement of PAR-2 in P. gingivalisinduced IL-33 mRNA expression.…”
Section: Role Of Par-2 In the Induction Of Il-33 By Gingipainsmentioning
confidence: 99%